Iran Mortality and Measures of Risk: Rankings for Public policy - M Aalabaf-Sabaghi (Tehran University of Medical Sciences, 2010)
Background: This paper offers mortality risk rankings for Iranian mortality data. It extends methods to include mixed cohorts, tests changes in mortality risks, compares measures of risk and discusses public policy implications. Methods: The methodology used in risk measures takes current practice and extends it to include variations in population dynamics. The specification is presented and compared with existing literature. Results: Our findings confirm literature results in the re-ordering that takes place when different risk measures are used. In addition, we find there is consistency in risk rankings between 1999 and 2000 records of Iranian mortality data.  Thus, these risk measures are stable, robust across time and relay risk information consistently. Conclusions: There are considerable implications in adopting particular risk measures for public policy. However, given properties of risk measures discussed here, it is clear that policy makers can select relevant risk measures depending on their priorities.